UJI AKTIVITAS ANTIULCER AIR ALKALI TERIONISASI PADA MENCIT PUTIH JANTAN (MUS MUSCULUS) - Adriyan Suhada; Bq. Fitria Maharani; Ni Komang Wijiani Yanti; Nur'aini Nur'aini (Lembaga Penelitian dan Pendidikan Mandala, 2021)
Alkaline water is water that has antioxidant content and has a structure that is rich in active hydrogen that can cure stomach ulcers. The purpose of this study was to determine the effectiveness of ionized alkaline water as an antiulcers in male white mice (mus musculus). Method of induction of gastric ulcer using aspirin, used as many as 24 male mice (mus musculus) aged 2-3 months used as mice test animals divided into 6 groups each group consisting of 3 animals all groups were given ulcer treatment for 7 days, then group I (negative control) were given aquadest group II (positive control) were given sucralfate, group III were given ph 8 alkaline water group IV was given ph 9.0 alkaline water, group V was given ph 9.5 alkaline water, and group VI was given alkaline water pH 11.5 treatment of each group for the next 7 days on the 14th day the mice were dissected and the gastric mucosa structure was observed and the mucosal damage value was determined. The results showed that alkaline water 9.5 and 11.5 had lower mucosal damage values than negative controls. It can be concluded that the alkaline water ph 9.5 and 11.5 are said to be effective in reducing gastric mucosal damage compared to the negative group given aquadest.